UWAGI O „ZŁOTEJ REGULE” AKUMULACJI KAPITAŁU RZECZOWEGO I LUDZKIEGO W KONTEKŚCIE ZAGADNIENIA MAKSYMALIZACJI DOBROBYTU - Pietraszewski, Piotr (Wydział Prawa i Administracji UAM, 2009)
The subject of the paper is social welfare maximisation in a neoclassical model of economic growth, extended by the accumulation of human capital. After introducing the model and characterising the behaviour of the economic system on the so-called balanced growth path, Phelps’ “golden rule of accumulation” is used to establish the values of the rates of investments (into real and human capital) maximising the level o f the long-term growth path of per capita consumption. At the same time the analytical limitations o f this conception in the context of the welfare maximisation is shown. Overcoming those limitations necessitates a direct reference to the preferences of individual economic agents over (per capita) consumption streams. Realisation of this demand finds its formal expression in formulating and solving a dynamic optimisation problem, based on the initial growth model. Finally, this procedure serves to find the specific character o f preferences of individual agents, in the light of which the values of investment rates resulting from Phelps’ rule are the optimal values (on the balanced growth path), for the achievement of which, according to the model, the economy should strive.
REMARKS ON THE “GOLDEN RULE” OF ACCUMULATION OF REAL AND HUMAN CAPITAL IN THE CONTEXT OF SOCIAL WELFARE MAXIMISATION